PENGARUH RASIO KEUANGAN PERBANKAN TERHADAP HARGA SAHAM BANK TERDAFTAR DI BEI - Muhamad, Ririn A.; Soleman, Rusman; Suwito (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2025)
The purpose of this study is to determine whether NPL, LDR, GCG, NIM, ROA, ROE, CAR & BOPO affect the stock prices of banking companies listed on the Indonesia Stock Exchange for the period 2018-2022. There are 47 populations in this study, using purposive sampling as a research method to obtain 12 samples. All financial ratio data are taken from the company's financial statements obtained from the official website of the Indonesia Stock Exchange (www.idx.co.id) The analysis technique used is multiple linear regression. Based on the results of the study, it shows that: Non-Performing Loans (NPL) have no effect on stock prices. Loan To Deposit Ratio (LDR) has no effect on stock prices. Good Corporate Governance (GCG) has a negative and significant effect on stock prices. Net Interest Margin (NIM) has a positive and significant effect on stock prices. Return On Assets (ROA) has a negative and significant effect on stock prices. Return On Equity (ROE) has a positive and significant effect on stock prices. Capital Adequacy Ratio (CAR) has no effect on stock prices. Operating Expenses Operating Income (BOPO) has a positive and significant effect on stock prices.